Usulan Perbaikan Efisiensi Operasional Melalui Pendekatan Seven Waste dan Metode 5S pada Bisnis Ritel (Studi Kasus: Koperasi UB) - Fakih, Mohammad Micko Hajj; Larutama, Wiku (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify operational waste based on the Seven Waste approach and to propose improvement strategies through the implementation of the 5S method in a retail business. The study employs a case study approach conducted at Koperasi UB, which operates with limited space where storage and product display areas are combined. The research methods include waste identification using the Seven Waste framework, root cause analysis through the 5 Whys method, and the formulation of improvement proposals using the 5S methodology. The results indicate that the dominant wastes are inventory waste, motion waste, and defect waste, caused by overstock conditions, ineffective layout, and the absence of standardized operational guidelines and demand forecasting. The proposed improvements focus on workspace arrangement, storage standardization, and the development of work discipline to enhance operational efficiency and minimize waste.